A systematic literature review on serious games evaluation: An application to software project management. (September 2015) - Calderón, Alejandro; Ruiz, Mercedes
Abstract: Training that future practitioners receive in software project management is a topic of great importance. The objective of this systematic literature review is to summarize the current state of the art of the different methods and procedures used to assess serious games. The review follows a predefined procedure that involves automatically searching well-known digital databases. 1199 papers were found by the automatic searches in the digital databases and 102 papers were selected as primary studies. The process was complemented with manual searches using author and backward snowballing techniques. Our systematic literature review identified the main methods followed to assess serious games, the application domains in which the assessments took place, the categories of serious games assessed, the main features considered to assess the educational effectiveness of serious games, the procedures followed for the assessments and the size of the population that participated in the assessments. The results are useful to researchers and practitioners willing to assess serious games in different fields, but specially to those interested in assessing serious games in the area of software project management. Highlights: We present a systematic literature review on serious games (SG) evaluation. We summarize the different methods and procedures used to assess SG. We observe the application domains and the categories of SG assessed. We identify the main methods, features, procedures and size of population to assess SG. Results are intended to be applied in the area of SG in software project management.